Wachsfabrik '89-'90. - Kisters, Jürgen; Wachsfabrik, Köln (Köln : Wachsfabrik, 1991)
Waechter, Roswita ; Mohr, Michael ; van Dokkum, Ronald ; Reuter, W. ; Hillebrand, C. ; Hillebrand, Elmar ; Ritter, Ali ; Brand, Rolf ; Berke, Sybille ; Kolbe, Martin ; Stapper, Josta ; Müller, Reinhard ; Koch, Wilhelm ; Nolden, Rolf ; Lückerath, Ulla ; Oraczewski, Jozef Krzystof ; Lamers, Hermann ; Moser, Harald ; Weimer, Birgitta ; Sorensen, Rolf ; Gerenton, Marc ; Wagner, Ulrich
biografie
Duits
boek